Rancang bangun rangka alat uji torsi sederhana berbasis eddy current menggunakan roller conveyor - Herakarsono, Alfianto; Gamayel, Adhes; Zaenudin, Mohamad (Jurnal Teknik Mesin Indonesia, 2024)
Testing the torque of a motorized vehicle, especially two-wheeled motorized vehicles (motorcycles), often requires equipment that is considered expensive and difficult to access on a small laboratory scale. However, the torque test is considered important to find out how a motorbike works using certain fuels, for example widely used fuel mixtures such as gasoline mixed with certain vegetable oils, to find alternative fuels. Therefore, a simple torque test tool is needed that can be designed and used as a preliminary study of alternative fuels. In this study, designed a simple eddy current-based torque test frame with a roller conveyor. Before the frame is formed, the frame design is outlined using the student version of ANSYS software to study the loading characteristics and promises. The simulation results show that the frame design can be used with a loading force of 294 N in the eddy current area and 981 N in the roller area. The frame was then manufactured using hollow iron measuring 4x6 cm with ASTM A500 material type. This research has succeeded in designing and producing a simple eddy current-based torque test frame using a roller conveyor.